Residential mobility and housing adjustment of older households in Europe - Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2006)
This paper investigates the determinants of residential mobility of older households (above 50 years old) and the adjustment of housing for those who move employing individual data from the European Community Household Panel. Although homeowners are less likely to move compared to renters, an increase in mobility rates is observed for older age homeowners. Moreover, having an outstanding home loan, retirement, the death of a spouse, and excessive housing costs, are significantly associated with a move in central and northern European countries, but not in the south. Analyzing the transitions from the current tenure choice after a move takes place, based on a competing risk hazard model, an increasing transition out of the current residence for old-age homeowners is found, indicating some dissaving later in life. The direction of the transitions is mostly from ownership to renting. However, especially in countries in central and northern Europe, transitions from ownership to ownership are also observed, which are associated with a reduction in the home size.
urn:nbn:de:101:1-2008072438
Keywords: 330